1997
DOI: 10.1042/bj3260449
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the labdane diterpene marrubiin in Marrubium vulgare via a non-mevalonate pathway

Abstract: The biosynthesis of the furanic labdane diterpene marrubiin has been studied in plantlets and shoot cultures of Marrubium vulgare(Lamiaceae). The use of [2-14C]acetate, [2-14C]pyruvate, [2-14C]mevalonic acid and [U-14C]glucose incorporation experiments showed that the labelling of sterols in etiolated shoot cultures of M. vulgare was in accordance with their biosynthesis via the acetate–mevalonate pathway. In contrast, the incorporation rates of these precursors into the diterpene marrubiin could not be explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 17 publications
2
32
0
2
Order By: Relevance
“…5,12,[16][17][18][19][20][21][22][23] The prenylation of the phydroxybenzoic acid involved in the formation of the chromenes 1 and 2 occurred via MEP pathway, suggesting that it is compartmentalized in the plastid. On the other hand, the second prenylation step would be occurred in the cytosol by MVA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…5,12,[16][17][18][19][20][21][22][23] The prenylation of the phydroxybenzoic acid involved in the formation of the chromenes 1 and 2 occurred via MEP pathway, suggesting that it is compartmentalized in the plastid. On the other hand, the second prenylation step would be occurred in the cytosol by MVA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, incorporation of 13 C-labeled Glc into plant cells (Eisenreich et al, 1996;Schwender et al, 1996;Arigoni et al, 1997;Knö ss et al, 1997;Lichtenthaler et al, 1997b) followed by NMR analysis led to new insights about the conversion of carbohydrate precursors into IPP. The new pathway proposes the condensation between the C2 unit from pyruvate and the C3 acceptor glyceraldehyde-3-phosphate to yield deoxy-xylulose phosphate, the nonmevalonic precursor of IPP Arigoni et al, 1997).…”
Section: The Role Of Transketolase In Generating Carbon-carbon Condenmentioning
confidence: 99%
“…Despite a long debate, a conclusive demonstration of mevalonic acid pathway reactions in plastids was still lacking (Gray, 1987). In vivo studies using 13 C-Glc labeling subsequently revealed the existence of an alternative nonmevalonic acid pathway for IPP synthesis in prokaryotes (Flesch and Rohmer, 1988;Rohmer et al, 1993Rohmer et al, , 1996 and in plants (Schwender et al, 1996;Arigoni et al, 1997;Knö ss et al, 1997;Lichtenthaler et al, 1997aLichtenthaler et al, , 1997b, which is initiated by a transketolation mechanism. We have characterized two pepper plastid transketolases, CapTKT1 and CapTKT2, and showed that they possess distinct specificities.…”
Section: Dedicated Roles Of Plastid Transketolasesmentioning
confidence: 99%
“…la, see e.g. [1]), and an alternative mevalonate independent biosynthetic route unravelled by 13 C-incorporation studies in bacteria [2], green algae [3][4][5][6][7][8], and higher plants [6,[8][9][10][11][12][13]. In fact, in higher plants and green algae the biosynthesis of all plastidic isoprenoids such as the phytyl side chain of chlorophylls, the carotenoids and the nonaprenyl side chain of plastoquinone-9 [3][4][5]12] appears to follow this alternative route, of which the elucidation of the distinct biosynthetic steps is just at the beginning.…”
Section: Introductionmentioning
confidence: 99%